Genetic Variability for Quantitative Characters in Vegetable Amaranthus (Amaranthus tricolor L.) - Jangde, Bhanupratap; Asati, Bhagwat Saran; Tripathy, Barsha; Bairwa, Pappu Lal; Kumar, Lav (International Journal of Bio-resource and Stress Management, 2018)
The present investigation on genetic variability in amaranthus (Amaranthus tricolor L.) Genotypes under Chhattisgarh plains was carried out at Pt. KLS College of Horticulture and Research Station, Rajnandgaon, Indira Gandhi Krishi Vishwavidyalaya, Raipur (C.G.) during kharif season 2015-16. The experiment was comprised of twenty three genotypes of amaranthus, laid out in Randomized Block Design (RBD) with three replications. Significant variations were recorded for the various characters studied. Widest range of variation was observed in Foliage yield (kg/plot) followed by harvest index(%), Leaf area, plant height and number of leaves per plant. Maximum genotypic and phenotypic coefficient of variation (GCV and PCV) was observed for Dry stem weight followed by Dry plant weight, harvest index (%), leaf stem ratio, Fresh stem weight. High magnitude of heritability was observed for Dry stem weight (91.7%) followed by Fresh stem weight (84.7%), Dry plant weight (84.6%), harvest index (83.3%) and leaf stem ratio (79.7%). The maximum genetic advance as percentage of mean was observed high for Dry stem weight (66.66%) followed by Dry plant weight (56.66%) and leaf stem ratio (50.57%). The highest heritability was recorded for the characters dry stem weight (91.7 %), fresh stem weight (84.7 %), dry plant weight (84.6 %), harvest index % (83.3 %), On the basis of this investigation selection criteria are Dry stem weight bringing out the improvement in amaranthus because they appearance with high value of GCV, PCV, heritability and genetic advance.